An alternative fluid dynamic explanation for propulsion in front crawl swimming - Toussaint, H. M. (coachesinfo.com, 2000)
Calculation of propulsion in front crawl swimming relies on the quasi-steady assumption that the fluid dynamic behaviour of a hand model in a flow channel (constant velocity and orientation) is similar to that of a hand of a real swimmer swimming the front crawl. It has been shown that quasi-steady calculations cannot account for the observed propulsive forces during front crawl swimming. Using woollen tufts the flow pattern around the arm and hand during the front crawl stroke was visualised. The flow direction varied strongly throughout the stroke and a strong, accelerating axial flow, not in the direction of the arm movement, was observed. These observations discredit the quasi-steady analysis of front crawl swimming. Instead, it is proposed that rotation of the arm leads to a proximo-distal pressure gradient, inducing axial flow. Such axial flow along the trailing side of the arm could greatly enhance the pressure difference over the hand, thus assisting propulsion by paddling.